2017
DOI: 10.1111/gcb.14009
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen‐rich microbial products provide new organo‐mineral associations for the stabilization of soil organic matter

Abstract: Understanding the cycling of C and N in soils is important for maintaining soil fertility while also decreasing greenhouse gas emissions, but much remains unknown about how organic matter (OM) is stabilized in soils. We used nano-scale secondary ion mass spectrometry (NanoSIMS) to investigate the changes in C and N in a Vertisol and an Alfisol incubated for 365 days with C and N pulse labeled lucerne (Medicago sativa L.) to discriminate new inputs of OM from the existing soil OM. We found that almost all OM wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(84 citation statements)
references
References 44 publications
(84 reference statements)
5
68
0
Order By: Relevance
“…Microbial efficiency-matrix stabilization hypothesis suggests that the microbial use effectiveness is governed by the stabilization through organo-mineral associations 59 . Nitrogen rich microbial products, due to their positively charged functional groups, favorably associate with mineral surfaces compared to C-rich moieties enhancing the storage of SOM 60 . The heterogeneous and complex distribution of N-based compounds observed in the NTR thin section (100-nm) could be partly indicating microbial contribution in associating SOM with soil mineral surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Microbial efficiency-matrix stabilization hypothesis suggests that the microbial use effectiveness is governed by the stabilization through organo-mineral associations 59 . Nitrogen rich microbial products, due to their positively charged functional groups, favorably associate with mineral surfaces compared to C-rich moieties enhancing the storage of SOM 60 . The heterogeneous and complex distribution of N-based compounds observed in the NTR thin section (100-nm) could be partly indicating microbial contribution in associating SOM with soil mineral surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a 365‐day incubation experiment, Kopittke et al. () reported, based on NanoSIMS, that microbial‐derived 15 N‐rich OM often adsorbed directly to mineral surfaces not previously associated with OM; but the contribution of inorganic N was not reported either. Other N compounds might only become sorbed in the subsoil as they are enriched in less sorptive hydrophilic DOM ( Kaiser and Zech , ) being disfavored from sorption in topsoil.…”
Section: Application Of the Multilayer Model In Soil Science And Relamentioning
confidence: 99%
“…The latter study shows that in subsoils 30-85% of total N were present as inorganic N. Further, the above mentioned changes in C/N ratios can also be attributed to the enrichment of N-rich microbial residuals on mineral surfaces via preferential adsorption. For example, in a 365-day incubation experiment, Kopittke et al (2018) reported, based on NanoSIMS, that microbial-derived 15 N-rich OM often adsorbed directly to mineral surfaces not previously associated with OM; but the contribution of inorganic N was not reported either. Other N compounds might only become sorbed in the subsoil as they are enriched in less sorptive hydrophilic DOM (Kaiser and Zech, 2000) being disfavored from sorption in topsoil.…”
Section: Strong Adsorption Of N-containing Compounds and Enrichment Omentioning
confidence: 99%
“…Yet, certain attributes of MAOM could make it a substantial N source. MAOM is enriched in low- Single average molecular-weight plant compounds (Haddix et al 2016) and microbial byproducts (Schmidt et al 2011;Miltner et al 2012;Kopittke et al 2017). MAOM thus possesses a low C/N ratio (Sollins et al 2006), which generally promotes N mineralization (Sollins et al 1984;Whalen et al 2000); this is in contrast to POM, which often has a relatively high C/N ratio and thus, early in its decomposition, acts as a sink for N (Whalen et al 2000;Luce et al 2011;Fornara et al 2011).…”
Section: Introductionmentioning
confidence: 99%